2020
DOI: 10.1007/s11069-020-04413-x
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic approach to estimating residential losses from different flood types

Abstract: Residential assets, comprising buildings and household contents, are a major source of direct flood losses. Existing damage models are mostly deterministic and limited to particular countries or flood types. Here, we compile building-level losses from Germany, Italy and the Netherlands covering a wide range of fluvial and pluvial flood events. Utilizing a Bayesian network (BN) for continuous variables, we find that relative losses (i.e. loss relative to exposure) to building structure and its contents could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…It is known that insurance claims can sometimes be subject to fraud or information distortion. In addition, variables related to the vulnerability of the assets like the construction characteristics, the materials, the quality, and the age of the structures (Paprotny et al, 2021) play important roles in determining whether a particular hydrodynamic is related to damage. This adds a degree of complexity to the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that insurance claims can sometimes be subject to fraud or information distortion. In addition, variables related to the vulnerability of the assets like the construction characteristics, the materials, the quality, and the age of the structures (Paprotny et al, 2021) play important roles in determining whether a particular hydrodynamic is related to damage. This adds a degree of complexity to the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well identified that claims are subject to fraud and information distortion. Also variables related with the vulnerability of the assets like the construction characteristics, the materials, the quality and the age of the structures (Paprotny et al, 2021) play an important role in whether for a particular hydrodynamic variable value damage occurs or not. This adds a degree of complexity to the analysis In addition to the sensitivity of results to resolution of the topographic and bathymetric data, the inclusion of thin flood walls via a land survey carried out by the authors also had a significant effect on the damage functions generated.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure analysis is carried out by intersecting flood maps and the polygonal shapefile of CH for each scenario. Exposure is also the value of the asset affected by the flood, for example, for residential buildings the market value or construction cost (Molinari et al, 2020; Paprotny et al, 2021). The value of CH is hardly monetizable, however the social appreciation and value of a cultural attraction, for example, a museum, a noble palace, a church etc.…”
Section: Methodsmentioning
confidence: 99%